Uma capitania dos novos tempos: economia, sociedade e política na São Paulo restaurada (1765-1822) - Ferlini, Vera Lucia Amaral (2009)
In this article, we reflect upon the history of the Captaincy of São Paulo as from 1750, drawing attention to its transformation from frontier land and "door to the backcountry" into a territory of strategic value for the purposes of conquest and defense of the southern regions, and economically integrated into the Atlantic trade routes.